Psalms of wonder: poems from the book of songs - Wallace, Carey (Presbyterian Publishing Corporation, 2023)
For readers of all ages, these inviting poems and gorgeous illustrations inspired by the book of Psalms echo all its wonder and courage, comfort and joy, protection and love.